2022
DOI: 10.1002/adem.202200918
|View full text |Cite
|
Sign up to set email alerts
|

Phase Continuity, Brittle to Ductile Transition Temperature, and Creep Behavior of a Eutectic Mo–20Si–52.8Ti Alloy

Abstract: Mo–Si–Ti alloys, like eutectic Mo–20Si–52.8Ti (at%), have previously been intensely investigated, owing to their excellent oxidation and creep resistance. To better understand high‐temperature mechanical behavior, a holistic assessment of microstructural features is necessary. Correspondingly, 3D‐focused ion beam tomography is carried out in Mo–20Si–52.8Ti. The results indicate a severely interconnected network of Mo solid solution (MoSS) and intermetallic (Ti,Mo)5Si3. Both phases retain similar network connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…(Mo, Ti) 5 SiB 2 phase exhibited the highest strength (5.9 GPa) followed by (Ti, Mo) 5 Si 3 (4.5 GPa) and then (Mo, Ti) ss (2.8 GPa). Nano-indentation studies have also shown that the highest hardness is exhibited by the (Mo, Ti) 5 SiB 2 phase followed by the (Ti, Mo) 5 Si 3 phase and then the (Mo, Ti) ss which agrees qualitatively with the observed trend of compressive strength ( Ref 28,29).…”
Section: Hardness and Elasticsupporting
confidence: 77%
See 1 more Smart Citation
“…(Mo, Ti) 5 SiB 2 phase exhibited the highest strength (5.9 GPa) followed by (Ti, Mo) 5 Si 3 (4.5 GPa) and then (Mo, Ti) ss (2.8 GPa). Nano-indentation studies have also shown that the highest hardness is exhibited by the (Mo, Ti) 5 SiB 2 phase followed by the (Ti, Mo) 5 Si 3 phase and then the (Mo, Ti) ss which agrees qualitatively with the observed trend of compressive strength ( Ref 28,29).…”
Section: Hardness and Elasticsupporting
confidence: 77%
“…The samples were irradiated using 3.5 MeV proton beam of $ 10 nA current. 429, 718 and 2125 keV prompt gamma rays from 10 B(p,ac)7Be, 1 0 B(p,p¢c) 10 B and 11 B(p,p¢c) 11 B, 983 keV of 4 8 Ti(p,p¢c) 48 Ti and 1273 and 1779 keV of 29 Si(p,p¢c)29Si and 28 Si(p,p¢c) 28 Si were detected during irradiation using HPGe detector for quantification of B, Ti and Si in the alloy. PIGE spectrum is shown in Fig.…”
Section: Microstructural Characterizationmentioning
confidence: 99%